2018
DOI: 10.1308/rcsfdj.2018.104
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to change: how much longer will our antibiotics work?

Abstract: Antimicrobial resistance (AMR) is the ability of bacteria to change, rendering antimicrobials (such as antibiotics, antivirals and antimalarials) ineffective in treating common infections, or as prophylaxis after major surgery or cancer treatment. The World Health Organization (WHO) predicts that these ‘superbugs’ will become a major threat to public health. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Three audit cycles conducted over 3 years at a British emergency dental service found that by reinforcing correct documentation (e.g. entering prescriptions into clinical notes with a diagnosis) and instituting a prescription logbook, the number of antibiotic prescriptions was reduced (dropping from 62% to 16%) with a commensurate increase in the use of local surgical intervention from 22% to 68% over the 3 year period …”
Section: Antibiotic Resistance and Dental Practicementioning
confidence: 99%
See 4 more Smart Citations
“…Three audit cycles conducted over 3 years at a British emergency dental service found that by reinforcing correct documentation (e.g. entering prescriptions into clinical notes with a diagnosis) and instituting a prescription logbook, the number of antibiotic prescriptions was reduced (dropping from 62% to 16%) with a commensurate increase in the use of local surgical intervention from 22% to 68% over the 3 year period …”
Section: Antibiotic Resistance and Dental Practicementioning
confidence: 99%
“…As prescribing health care professionals, dentists should not underestimate their contribution to antibiotic resistance -66% of antibiotics prescribed in a dental setting are not clinically indicated. 1 Dentists should be powerful advocates for change by challenging the prevailing attitudes to the use of antibiotics in the community and limiting our role in exacerbating resistance. Prevention is central to disease control in modern dentistry, thus, we are well placed to embrace the challenge of antibiotic resistance at the chairside by following guidelines 46 which emphasize:…”
Section: Antibiotic Resistance and Dental Practicementioning
confidence: 99%
See 3 more Smart Citations